2010
DOI: 10.1097/smj.0b013e3181de0ce0
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Steatohepatitis: A Review of the Literature and Updates in Management

Abstract: Nonalcoholic steatohepatitis is a common cause of liver inflammation and is associated with obesity, insulin resistance, and hyperlipidemia. There are concerns that it may turn out to be the most common cause of liver failure as prevalence of obesity increases. It leads to increased morbidity and mortality. Other causes of liver inflammation, especially alcoholic liver disease, must be ruled out. The diagnosis is suggested by abnormalities in the blood work and metabolic panel in an obese patient. Despite adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…It is reported that almost 10% ~ 20% of individuals with NAFLD have NASH, 10% ~ 15% of individuals with NASH progress to cirrhosis [14]. In patients with cirrhotic NASH, HCC and liver failure are the main causes of morbidity and mortality (5-year cumulative HCC development rate 11.3%, 5-year survival rate 75.2%, respectively) [15].…”
Section: Backgroundsmentioning
confidence: 99%
“…It is reported that almost 10% ~ 20% of individuals with NAFLD have NASH, 10% ~ 15% of individuals with NASH progress to cirrhosis [14]. In patients with cirrhotic NASH, HCC and liver failure are the main causes of morbidity and mortality (5-year cumulative HCC development rate 11.3%, 5-year survival rate 75.2%, respectively) [15].…”
Section: Backgroundsmentioning
confidence: 99%
“…Other treatment approaches include special diets, antioxidants, and cytoprotective therapy [ 3 ]. In the 1990s, the incidence of NAFLD and NASH began to increase in both adults and children, in parallel with the rise in obesity rates, and are now widely recognized pathological conditions [ 4 ]. The estimated prevalence rates of NAFLD and NASH are 20–30 and 3.5–5 %, respectively [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with NASH, moreover, have reduced survival rates [ 6 ]. As the prevalence of NASH threatens to increase further, many medications are being evaluated, targeting different steps in the development of hepatic steatosis or its progression to steatohepatitis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to an increased average life span, present generations of women can expect to spend at least a third of their lives in the postmenopausal state [4]. Dietary and lifestyle guidelines to reduce overall body weight may help avoid NAFLD, however, there are no specific drugs to treat this liver disease [5].…”
Section: Introductionmentioning
confidence: 99%